Pediatric Cardiac Magnetic Resonance Reference Values for Biventricular Volumes Derived From Different Contouring Techniques. Issue 3 (17th June 2022) - Voges, Inga; Caliebe, Amke; Hinz, Sophia; Boroni Grazioli, Simona; Gabbert, Dominik D.; Daubeney, Piers E. F.; Uebing, Anselm S.; Pennell, Dudley J.; Krupickova, Sylvia
Abstract : Background: Measurement of ventricular volumes and function using MRI is an important tool in pediatric congenital heart disease. However, normal values for children are sparce and analysis methods are inconsistent. Purpose: To propose biventricular reference values in children for two MRI postprocessing (contouring) techniques. Study Type: Retrospective. Subjects: A total of 154 children from two institutions (13.9 ± 2.8 years; 101 male) that were referred for a clinical MRI study. Field Strength/Sequence: 1.5 T; balanced steady‐state free precession (bSSFP) sequence. Assessment: Left ventricular (LV) and right ventricular (RV) end‐diastolic and end‐systolic volumes (LVEDV, LVESV, RVEDV, RVESV) and end‐diastolic and end‐systolic myocardial mass (LVEDMM, LVESMM, RVEDMM, RVESMM) were measured from short‐axis images using two contouring techniques: 1) papillary muscles, trabeculations and the moderator band were included in the ventricular blood volume and excluded from the myocardial mass, 2) papillary muscles, trabeculations and the moderator band were excluded from the ventricular volume and included in the ventricular mass. Statistical Tests: Univariable and multivariable linear regression models were used to evaluate relationships between sex, weight, height, body surface area (BSA) and age and volumetric results. Reference graphs and tables were created with the LMS‐method. Contouring techniques were compared by intraclass correlation, regression analysis and Bland–Altman plots. A P value < 0.05 was considered statistically significant. Results: Height and BSA were significantly associated with LVESV (method 1) and with LVEDV and RVEDV (method 2). LVESV (method 2), RVESV (both methods), RVEDV (method 1), and LVEDMM and RVEDMM (both methods), showed significant associations with height and weight. LVSV and RVSV (both methods) were significantly associated with BSA and weight. RVESV (method 1) was significantly associated with age. Gender showed significant associations for all parameters. Data Conclusion: The proposed pediatric reference values can be used in the diagnosis and follow‐up of congenital or acquired heart disease and for research purposes. Evidence Level: 3 Technical Efficacy: Stage 2